Respons Pertumbuhan Dan Hasil Pada Dua Varietas Tanaman Caisim Akibat Pemberian Takaran Pupuk Nitrogen - Sumarna, Nana; Sondari, Nunung; Widodo , R. Wahyono (OrchidAgro, 2024)
This research aims to study the growth response and yield of two different varieties of caisim plants and what the optimal nitrogen rate is to produce net fresh weight per plot. The research was conducted in the rice fields of Babakan Pameungpeuk Village, Wanasari Village, Wanayasa District, Purwakarta Regency. The height of the place is 650 meters above sea level September - October 2023. The research design used is a Split Plot Design which consists of 2 factors and each factor consists of 2 levels of treatment, the first factor is V = Variety, of which v1 = Shinta F1, v2 = Dora. The second factor is N = dose of ameliorant plus, namely n0 = 0 kg N/0 kg Urea ha1, n1 = 92 kg N/200 kg Urea ha-1, n2 = 184 kg N/400 kg Urea ha-1, n3 = 276 kg N/600 kg Urea ha-1, n4 = 368 kg N/800 kg Urea ha-1, The same replication was placed in the same place towards East-West with the experimental layout. The results of the research showed that there was a real interaction between the main plot of plant varieties and sub-plots of nitrogen fertilizer dosage on observations of root volume, root decay ratio, gross fresh weight per plant, net fresh weight per plant, gross fresh weight per plot and net fresh weight per plot, the optimum dose of nitrogen fertilizer to produce net fresh weight per plant.Keywords: Nitrogen Fertilizer, Caisim Plants, Varieties